Apoptotic Effects of Hypericum dogonbadanicum on Lung and Gastric Cancer Cell Lines - Maddah, Seyyedeh Mahdokht; Mostafavi, Golaleh; Vaali, Masoud; Ranjbar, Ehsan (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: Cancer is the second deadliest disease worldwide. Medicinal plants have been recognized for their cytotoxic and antitumor properties. This study aimed to assess the potential anticancer effects of the hydroalcoholic extract and essential oil of an Iranian endemic species, Hypericum dogonbadanicum, on AGS, A549 and a normal cell and the novel investigation of changes in caspase-3 and caspase-8 genes expression level. Materials and Methods: The essential oil and extract were extracted using Clevenger and Maceration techniques respectively. Their components were determined employing GC/MS and HPLC methods. The evaluation of gene expression levels was accomplished by a quantitative PCR method. Results: According to MTT assay data, it was observed that the IC50 value for the essential oil was 200 μg/mL. However, for the extract, the IC50 values were different, with a value of 50 μg/mL after 72 hr of treatment in A549 cells and a value of 200 μg/mL after 48 hr of treatment in AGS cells. The Apoptosis analysis showed a notable rise in the numbers of both early and late apoptotic cells in both cell lines upon treatment with the extract and essential oil. Furthermore, when exposed to the extract, there was an observed overexpression pattern in both caspase-3 and caspase-8 genes in both cell lines. However, the essential oil effects led to significant upregulation of these genes only in AGS cells. Conclusion: Based on our findings, H. dogonbadanicum extract and essential oil give promising results as apoptotic inducers for both cancer cell lines via targeting and increasing caspase-3 and caspase-8 gene expression.
Keywords: Cytotoxic; Essential oil; Ethanolic extract; Gene expression; Hypericum dogonbadanicum